Influence of Body Mass Index on Compensatory Sweating in Patients after Thoracic Sympathectomy due to Palmar Hyperhidrosis - Dobosz, Lukasz; Cwalina, Natalia; Stefaniak, Tomasz (The Thoracic and Cardiovascular Surgeon, 2017)
Background Thoracic sympathectomy (TS) is one of the most effective methods of treatment of primary hyperhidrosis. One of the side effects of this procedure is compensatory sweating (CS).Objective The aim of our study was to evaluate the influence of body mass index (BMI) on CS in patients after TS due to palmar hyperhidrosis.Methods Data from 157 patients with palmar hyperhidrosis who underwent TS were collected. The patients were subsequently divided in two groups according to their initial BMI: group A, BMI < 25 kg/m2, and group B, BMI ≥ 25 kg/m2. Objective (gravimetry) and subjective (VAS) measurements of the intensity of hyperhidrosis were taken from the patients' bodies prior to surgery, as well as 3 and 12 months after TS.Results Average palmar hyperhidrosis levels before the surgery did not differ significantly between the two groups (238.65 vs. 190.15; p = 0.053). A statistically significant decrease in palmar hyperhidrosis was noted in both groups, both 3 and 12 months after surgery (238.65 vs. 11.86 vs. 13.5; p < 0.05, and 190.15 vs. 16.67 vs. 11.81; p < 0.05, respectively). The intensity of sweating over the abdomino-lumbar area differed significantly between the groups before the surgery, both in subjective (1.71 vs. 3.61; p < 0.05) and objective (13.57 vs. 35.95; p < 0.05) evaluations. Three months after surgical intervention, an intensification of CS was observed in both the groups; however, no statistically significant differences were observed between the two sets of patients (VAS: 4.58 vs. 5.16; p = 0.38; gravimetry: 33.87 vs. 53.89; p = 0.12). Twelve months after TS, CS was higher in the group with an initial BMI ≥ 25 kg/m2, both in subjective and objective evaluations (3.23 vs. 4.94; p = 0.03 and 18.08 vs. 80.21; p = 0.026, respectively).Conclusion Patients with a BMI ≥ 25 kg/m2 experience more severe CS after TS, both in subjective and objective evaluations.
Keywords: hyperhidrosis; thoracoscopy/video-assisted thoracoscopic surgery; compensatory sweating; sympathectomy